2013
DOI: 10.1039/c3nr04271e
|View full text |Cite
|
Sign up to set email alerts
|

Mesoporous ZnCo2O4 nanoflakes with bifunctional electrocatalytic activities toward efficiencies of rechargeable lithium–oxygen batteries in aprotic media

Abstract: This study reports the successful synthesis of ternary spinel-based ZnCo2O4 nanoflakes (NFs) with mesoporous architectures via the combination of a urea-assisted hydrothermal reaction with calcination in an air atmosphere. Owing to their favorable mesostructures and desirable bifunctional oxygen reduction and evolution activities, the resulting mesoporous ZnCo2O4 NFs yielded stable cyclability at a cut-off capacity of 500 mA h gcarbon(-1) in the case of aprotic Li-O2 batteries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
53
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(54 citation statements)
references
References 38 publications
(35 reference statements)
1
53
0
Order By: Relevance
“…Co 3 O 4 was reported as a promoter to enhance the interfacial transport of LiO 2 , which imply that the favorable interaction between LiO 2 and Co-based oxides may protect carbon materials from oxidative decomposition during charge process20. Although substantial recent studies on cobalt-based oxide materials have exhibited better cycle performance, most of them attribute the improved cycle performance to the conventional electrocatalytic activity and the nanostructure of cathodes92122232425. Up to date, there is still rare report concerning the adsorption configuration of Co-based oxides with LiO 2 as a factor for enhancing the cycle performance26.…”
mentioning
confidence: 99%
“…Co 3 O 4 was reported as a promoter to enhance the interfacial transport of LiO 2 , which imply that the favorable interaction between LiO 2 and Co-based oxides may protect carbon materials from oxidative decomposition during charge process20. Although substantial recent studies on cobalt-based oxide materials have exhibited better cycle performance, most of them attribute the improved cycle performance to the conventional electrocatalytic activity and the nanostructure of cathodes92122232425. Up to date, there is still rare report concerning the adsorption configuration of Co-based oxides with LiO 2 as a factor for enhancing the cycle performance26.…”
mentioning
confidence: 99%
“…The ZCO + SWCNT mixture was not tested under this capacity-limited protocol because it had ap oorer cycling performance than the ZCO/SWCNT composite in the full discharge/charge protocol. The ZCO/ SWCNT composite electrodes reported herein demonstrate superior electrochemical performances to reported air electrodes made with ZCO nanoflakes, [32] NiCo 2 O 4 ,a nd MnCo 2 O 4 , [25][26][27][28][29] as shown in Ta ble S1 in the Supporting Information. At the same time, the ZCO/SWCNTc omposite electrode retains almost the same discharge/charge voltage profilesf or 50 cycles and leads to quite stable cycling performance at ac onstant capacity of 800 mAh g À1 within the cutoff voltages.…”
Section: Resultsmentioning
confidence: 85%
“…Many catalysts have been developed forL i-O 2 batteries, such as carbon nanotubes, nanofibers, or carbides; [3,[10][11][12][13] graphene; [14,15] metal oxides; [16][17][18] noble metals; [19][20][21][22] and perovskites. [32] However,t hey ex situ mixed the preprepared ZCO catalyst with Super Pc onductive carbon( referred to as ZCO + SP) and poly(vinylidene fluoride) (PVDF) bindert om ake air electrodes, which did not allow the ZCO nanoflakes to function well as ac atalyst;t hererfore, only very limitedc apacity (500 mAh g À1 )a nd limited cycle life (30 cycles) were obtained. [25][26][27][28][29][30][31] Hung et al also reported the use of ZnCo 2 O 4 (ZCO) as ab ifunctional catalystf or Li-O 2 batteries.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the O1s spectrum, as shown in Fig. 4d, two peaks 529.7 and 531.3 eV corresponded to the oxygen species of the Co-O and Zn-O bands in ZnCo 2 O 4 [30]. The specific surface area and porous nature of multiporous ZnCo 2 O 4 microspheres are further characterized by Brunauer-Emmett-Teller (BET) analysis using N 2 adsorption-desorption isotherm, as shown in Fig.…”
Section: Structural Characterization Of Multiporous Znco 2 O 4 Microsmentioning
confidence: 98%